Persepsi, Preferensi dan Perilaku Masyarakat Terhadap Konsep Ecodesign Lanskap Permukiman - Priambudi Trie Putra (Unika Soegijapranata Semarang, 2018)
Population growth in large cities in Indonesia increased demand for housing in urban areas. It might cause in interference to natural landscape of the city. Cities are required to be a comfortable inhabited place and concern to environmental sustainability. Ecodesign concept approach planning is an alternative that could be done to improve quality of the environment. The principle of ecodesign concept is the integration design in designing environment that integrates man-made design with natural design. The method used was collecting residents’ perception in three urban housing in West Bogor District, Bogor City, which are Bumi Menteng Asri, Griya Melati, and Pakuan Regency. There are two aspects related with ecodesign concept: ecodesign concept micro scale and ecodesign concept macro scale. Based on the survey (n = 90), only 39% of the respondents know about the definition of ecodesign concept of settlement landscape. Although most of respondents don’t know about the concept, there are still evidence of behaviors related with ecodesign concept. Generally, the ecological and esthetical condition in those three study location are in good condition. The result of correlation test shows that there is no any significant correlation between perception, preference, and behavior. Ecology and esthetic aspect are correlated positively only at Bumi Menteng Asri. Participation from the user is the main factor in order to create ecodesign concept of settlement landscape.